Effects and sustainability of a 13-day high-intensity shock microcycle in soccer - Wahl, P.; Güldner, M.; Mester, J. (Journal of Sports Science & Medicine, 2014)
The preseason in soccer is a short period of 6-8 weeks where conditional abilities, technical and tactical elements need to be trained. Therefore, time is lacking to perform long term preparation periods for different abilities, especially endurance training. There is evidence that the implementation of high-intensity shock microcycles in preseason training could be one way to improve physical performance in a short period of time. Therefore, the purpose of the present study was to examine the effects and the sustainability of a high-intensity shock microcycle on soccer specific performance. Over 2 weeks, 12 male soccer players (26.1 ± 4.5 years) performed 12 high-intensity training (HIT) sessions in addition to their usual training. Before (pre), 6 days (6d) and 25 days (25d) after training, subjects performed Counter Movement Jump (CMJ), Repeated-Sprint Ability (RSA) test and Yo-Yo Intermittent Recovery Test Level 2 (YYIR2). Mean sprint time (RSAMean) (cohen`s d = -1.15), percentage decrement score (RSAIndex) (cohen`s d = -1.99) and YYIR2 (cohen`s d = +1.92) improved significantly from pre to 6d. 25d after, values showed a significant reduction for YYIR2 (cohen`s d = -0.81) and small to moderate but not significant increase for RSAMean (cohen`s d = +0.37) and RSAIndex (cohen`s d = +0.7) compared to 6d values. Small but no significant increases were found for CMJ (cohen`s d = +0.33) and no significant and substantial changes were found for RSABest (cohen`s d = -0.07) from pre to 6d. For competitive soccer players, block periodization of HIT offers a promising way to largely improve RSA and YYIR2 in a short period of time. Despite moderate to large decreases in RSAIndex and YYIR2 performance in the 19 day period without HIT, values still remained significantly higher 25d after the last HIT session compared to pre-values. However, it might be necessary to include isolated high-intensity sessions after a HIT training block in order to maintain the higher level of YYIR2 and RSAIndex performance.